2020
DOI: 10.1177/0300060520977382
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical characteristics of patients with recurrent psychiatric readmissions in Qatar

Abstract: Objective To examine the sociodemographic and clinical characteristics of psychiatric patients with recurrent psychiatric readmissions (RPR). Methods A retrospective study was conducted at Hamad General Hospital in Qatar on psychiatric patients with recurrent readmissions from August 2018 to January 2019. Results Of 380 psychiatric patients admitted during the study period, 40 (10.5%) were readmitted within 30 days of discharge. Most of the patients who were readmitted were single, male and unemployed. Psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Six studies (6) [ 25 , 26 ] reported that hospitalization characterized with short periods of inpatient stay, especially for first admitted patients, were associated with higher risk of readmission [ 27 ]. The short length of stays can be helpful in reducing costs in managing patients in the early stages of mental disorders [ 26 , 27 ] when there is an effective integration between inpatient units and community-based services [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies (6) [ 25 , 26 ] reported that hospitalization characterized with short periods of inpatient stay, especially for first admitted patients, were associated with higher risk of readmission [ 27 ]. The short length of stays can be helpful in reducing costs in managing patients in the early stages of mental disorders [ 26 , 27 ] when there is an effective integration between inpatient units and community-based services [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The short length of stays can be helpful in reducing costs in managing patients in the early stages of mental disorders [ 26 , 27 ] when there is an effective integration between inpatient units and community-based services [ 26 ]. The risk of readmission was higher in the periods immediately after discharge [ 28 ]; the further away from the discharge, the lower the risk of a new admission [ 25 ]. In a study [ 29 ] conducted and published by Tedeschi et al, 2019, the predictors for readmission were a shorter length of stay (LoS); the protective factors identified in the study were young age, involuntary admission, and the intermediate number of public healthcare staff available (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of routine follow-up care provided after clients are discharged from acute care units may lead to detrimental effects, including readmission and frequent emergency visits [ 12 , 13 ]. An estimated 12–22% of discharges from mental health hospitalizations may result in subsequent emergency department (ED) visits and 5–50% in hospital readmission depending on age and mental health conditions [ 14 , 15 , 16 , 17 , 18 ]. Several factors, including prior psychiatric hospitalization, multiple comorbidities, unemployment, and psychosis, have been identified as likely primary drivers of readmission within four years after hospital discharge [ 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%